Proses Pembuatan Gamelan Awi Karya Mang Dedi Kab. Sumedang - Koncara, Braja Musti (LP2M ISBI Bandung, 2022)
Gamelan Awi is a traditional musical instrument from Sundanese which is the result of an adaptation of a metal-based gamelan. Mang Dedi is one of the bamboo gamelan craftsmen with a form that adapts other Sundanese bamboo musical instruments. In this innovation, Mang Dedi managed to make a gamelan at a low price, this has the potential to preserve bronze gamelan which is rarely found and even very few people have it.